Optimization of Women's Reproductive Health as Victims of Domestic Abbusive Through Android Application in Medan City - Asiah, Nur; Syahrin, Alvi; Suza, Dewi Elizadiani (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The increasing number of domestic violence cases so far, especially during COVID-19 in Medan City, makes there no longer a safe zone for children and women, especially housewives. Based on LBH APIK data that Medan City is in the red zone for domestic violence cases. With these economic difficulties, it is very risky for domestic violence, especially in the Covid-19 pandemic period which is recommended by the Government to stay at home or reduce employees in complying with Prokes, so that many companies or other businesses experience a major slump or loss. From the observation of the team also get many housewives who are just silent and do not report cases of domestic violence this is due to fear, shame and lack of knowledge. The methods used in this devotion are: 1. Health education with reproductive health materials of domestic violence victims; 2. PKPA staff training; 3. Assistance of PKPA staff in conducting reproductive health counseling to domestic violence victims; 4. Evaluation of program success: pre test and post test of PKPA staff and domestic violence victims of extension participants; 5. Socialization and training in application use Android-based prototype. The external target of this community service program activity is the formation of a group of women who become educators of Reproductive Health of women victims of domestic violence; Reproductive health module of KDRT victims, publication in issn-based journal, Video activities (youtube) and Harian Waspada Medan, Android Prototype Application, UU PKDRT.